Dissemination and Documentation of Pakpak Traditional Music for the Preservation and Development of Cultural Values - Irfan Simatupang; Lister Berutu; Yoe Anto Ginting; Nurbani Nurbani (INFOKUM, 2026)
Pakpak traditional music is an integral part of the cultural heritage of the Pakpak ethnic community in North Sumatra, Indonesia. However, rapid social change, globalization, and declining intergenerational transmission have posed serious challenges to its sustainability. This study aims to disseminate and document Pakpak traditional music as a strategic effort to preserve and develop its cultural values. The activities were conducted through field observations, audio-visual documentation, interviews with traditional musicians and cultural leaders, and community-based workshops involving local youth and cultural practitioners. The documentation process focused on musical instruments, performance structures, symbolic meanings, and the social functions of Pakpak traditional music within community rituals and daily life. The results indicate that systematic dissemination through digital media and educational activities significantly increases community awareness and appreciation of Pakpak traditional music. Moreover, the documentation serves as an important cultural archive that supports cultural education, research, and future revitalization efforts. This study concludes that dissemination and documentation are essential approaches for sustaining Pakpak traditional music and strengthening local cultural identity in the face of modern cultural transformations.